Spinal cord compression in patients with mucopolysaccharidosis - Pantel, Tobias; Lindschau, Mona; Luebke, Andreas M.; Kunkel, Philip Oskar Sean; Dreimann, Marc; Muschol, Nicole; Eicker, Sven O. (European spine journal, 2022)
Spinal abnormalities frequently occur in patients with mucopolysaccharidosis (MPS) types I, II, IV, and VI. The symptoms are manifold, which sometimes prolongs the diagnostic process and delays therapy. Spinal stenosis (SS) with spinal cord compression due to bone malformations and an accumulation of storage material in soft tissue are serious complications of MPS disease. Data on optimal perioperative therapeutic care of SS is limited.
Gesehen am 12.12.2023